PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X MAN 2 PONTIANAK - Aulia, Zakiah; Ulfah, Maria; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study is aimed at determining the effect of using the problem-based learning model towards the students’ critical thinking skill in the 10th-grade History subject at MAN 2 Pontianak. The method used in this study is experimental with a quasi-experimental design, of which the discussion is presented quantitatively. The sample was taken by applying a purposive sampling technique. The subjects of the research are the 10th-grade Science students of MAN Pontianak. 38 participated in the developed learning model training (experimental group) and the other 38 participated in the control group. The data were collected through direct observation, test, and documentary study. The tools used in data collection are observation sheet for student activities, test sheets in the form of essay, and the field notes used in the interview. The data were analyzed statistically. The result from the t-test shows that the Sig. value (2-tailed) by 0.000 greater than 0.05, with the t-count by 5.641. Therefore, it can be concluded that there is an effect on the use of problem-based learning model towards students’ critical thinking skill in the 10th-grade History subject at MAN 2 Pontianak, of which the effect size obtained is 0.44 with a medium category.  Keywords:  Problem-based learning model, critical thinking skills, History subject